Application of Hexagon's Fraud Theory In Detecting The Tendency Of Fraud In Village Fund Management in Kerinci Regency With Religiosity As A Moderation Variable - Anisa Rizki; Enggar Diah Puspa Arum; Nela Safelia (International Journal of Business and Quality Research, 2023)
The purpose of this study is to determine the influence of hexagon fraud theory on the tendency of fraudulent village fund management in Kerinci Regency with religiosity as a moderation variable. Based on the type of data, this research is a type of quantitative research. The data collection method in this study used a questionnaire, which was carried out by dividing a list of questions to respondents so that these respondents provided answers. The results of this study are that the variables of capability, opportunity, and ego have a significant effect on the tendency of fraud in village fund management in Kerinci Regency. While the variables stimulus, collusion, rationalization do not affect the tendency of fraud in village fund management in Kerinci Regency. Furthermore, the variable of religiosity is only able to moderate the influence between opportunity and fraud tendencies. While the variables stimulus, capability, collusion, rationalization, and ego, religiosity is unable to moderate its effect on the tendency of fraud in village fund management in Kerinci Regency.